Souhir Zekri Masson. Mapping Metabiographical Heartlands in Marina Warner's Fiction - Chantal Zabus (European Journal of Life Writing, 2020)
Souhir Zekri’s book makes up for the relative neglect around British author and public intellectual Marina Warner’s oeuvre, which started receiving critical attention only a decade and a half ago.